The Analgesic Museum - Koebner, Ian J.; Bonilla, Bethney; Slatman, Jenny; Parry, Manon (Frontiers in Pain Research, 2022)
This manuscript uses the perspectives and insights that emerged from the Analgesic Museum conference held virtually on March 11, 2022 as a mechanism for considering the role museums and artists can play in the public health effort to reduce the burden of persistent pain. One hundred and fifty-seven individuals from 22 countries registered for the Analgesic Museum conference. The event explored the intersection of art and pain management practices with presentations centered on three domains of interest: exhibition development, arts experiences and practices, and research and creative scholarship.